A Calcineurin Regulator MoRCN1 Is Important for Asexual Development, Stress Response, and Plant Infection of Magnaporthe oryzae - Liu, Caiyun; Liu, Tiangu; Lv, Ziwei; Qin, Mengyuan; Qu, Zhiguang; Zhang, Ziwei; Li, Fuyan; Chen, Deng; Zhang, Xinrong; Chen, Xiao-Lin; Shen, Mi (Frontiers in Plant Science, 2022)
The calcium/calcineurin signaling pathway plays a key role in the development and virulence of plant pathogenic fungi, but the regulation of this signaling pathway is still not clear. In this study, we identified a calcineurin regulator MoRCN1 in the plant pathogenic fungus Magnaporthe oryzae and found it is important for virulence by regulating the calcineurin pathway. MoRCN1 deletion mutants were severely decreased in colony growth and conidia formation. More importantly, the deletion of MoRCN1 led to a significant reduction in virulence due to defects in appressorium formation and invasive growth. The ΔMorcn1 mutants were more sensitive to different stresses and induced host ROS accumulation, suggesting a role of MoRCN1 in stress adaptation. We found that MoRCN1 directly interacted with the calcineurin catalytic subunit MoCNA and affected its protein stability, which was therefore important for regulating the calcineurin pathway. Transcriptome analysis showed that MoRCN1 significantly activated 491 genes and suppressed 337 genes in response to calcium ion, partially overlapped with the MoCRZ1-bound genes. Gene Ontology and KEGG pathway analyses indicated that MoRCN1-regulated genes were enriched in stress adaptation, lipid metabolism, and secondary metabolite biosynthesis, reflecting a function of MoRCN1 in host cell adaptation. Altogether, these results suggest MoRCN1 functions as a regulator of the calcium/calcineurin signaling pathway for fungal development and infection of host cells.